Exploration the Quality of Life and the related factors in women with recent diagnosis of gynecological cancer, before the surgical treatment, in Greece - Fasoi, Georgia; Bourazani, Maria; Papatheodorou, Dimitris; Vlachou, Eugenia; Toylia, Georgia; Kaba, Evridiki; Lalou, Panagiota; Sotnikova, Christina; Kelesi, Martha (Health & Research Journal, 2020)
Introduction: In Greece, it is estimated that annually 600 new cases of cervical cancer are diagnosed, being the third most common form of cancer in women after breast cancer (22.9%) and colon cancer (9.4%).In addition to being life-threatening, such a diagnosis can also represent the psychological impact of gynecological cancers; there are negative emotional consequences of such a diagnosis for both patients and their families affecting the quality of life (QOL) of patients with gynecological cancer. Aim: To examine the quality of life (QOL) of women with recent diagnosis of gynecologic cancer (RDGC) in Greece during their illness and to identify the psychosocial problems and the symptoms faced by women in the early stages of the disease. Material and Method: A prospective study of 63 patients with RDGC before undergoing hysterectomy, who completed the EORTC QLQ-C30 questionnaire. Results: The patients were between 45 and 50 years old (19.6%). Impaired physical functioning of women with RDGC was associated with strenuous activity or a long walk. Emotionally, patients showed a lack of concentration, tension, anxiety, irritation and depression. Age was negatively correlated with depression (p-value = 0.05<0.1). More than half of women had pain and few of them suffered a lot. Pain, shortness of breath (dyspnea) and fatigue caused discomfort and interference with daily living activities. More than half had sleeping disorders. Constipation and lack of appetite were common symptoms of the digestive system. Most women had no social or financial problems and rated their quality of life “very good”. Conclusions: Women with a RDGC, besides the common physical symptoms such as fatigue, pain, anorexia, sleep disorders and loss of appetite, had also emotional disorders. The feeling of depression was present in most patients. It was found that the younger the patient, the more depressed they feel.